Analysis of Relationship Between Self Efficacy and Resilience on Kip-Kuliah Students Learning Outcomes - Yahya Nur Ifriza; Istijabah Ifti Mufsiroh; Amalina Shabrina; Nurul Faizah; Sri Murti Retnoningrum (Publikasi Indonesia, 2025)
The KIP-Kuliah scholarship program aims to support underprivileged Indonesian students in higher education, yet the psychological factors influencing their success remain underexplored. This study investigates the interplay between self-efficacy and resilience in shaping academic and non-academic outcomes among KIP-Kuliah recipients. The research aims to (1) analyze the relationship between self-efficacy and resilience, and (2) assess their combined impact on learning achievements. A mixed-methods approach was employed, combining quantitative surveys (n=100) and qualitative interviews (n=10) with KIP-Kuliah students at Universitas Negeri Semarang. Statistical analyses (correlation, regression) and thematic interviews were conducted. Results revealed a strong positive correlation (r=0.678, p<0.01) between self-efficacy and resilience. Qualitative data underscored the role of financial aid, social support, and organizational involvement in enhancing these traits. The study highlights the need for integrated support programs that address both financial and psychological barriers. Recommendations include tailored mentoring and policy enhancements to maximize the KIP-Kuliah program’s impact.